CARLO VENTRESCA’S AMBITION THAT LEADS TO DESTRUCTION IN DAN BROWN’S ANGELS&DEMONS - Saâ€™adah, Fadlilatus (LANTERN (Journal on English Language, Culture and Literature), 2015)
Every human has aspirations hopes, and purposes to reach in their lives. Sometimes people break the norm, ethic, rule, and law to reach their ambition. The purpose of this study is to analyze Carlo Ventresca in Dan Brown’s Angels&Demons in his efforts to reach his ambition to become a pope. His ambition leads to destruction to other people and also for himself. This study uses library research and psychological approach in the analysis of this novel. Carlo Ventresca has conflicts within himself and against other people. His efforts to reach his ambition include breaking the law and moral ethics. He even kills. However he fails to reach his ambition and finally commits suicide. His ambition leads to destruction to people around him, the church, the public and even himself. He experiences moral, mental, and physical destructions. Unrestrained ambition by the bad ways will result the failure and leads to destruction.